2020
DOI: 10.1016/j.jmst.2019.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of sulfur hydrophobized plasmonic photocatalyst towards durable superhydrophobic coating material

Abstract: The widely used photocatalytic self-cleaning coating materials are often made of polymers and polymer based composites, where the photocatalyst immobilization occurs with macromolecules. However, these organic polymers are often unstable under exposure to UV irradiation and easily degraded by reactive radicals produced in the photocatalytic reaction. In order to solve this problem, in this paper, we present the facile preparation of a multifunctional coating with dual superhydrophobic and photocatalytic proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The main advantages of these biomass materials are cheap, rich resources and easy availability. 21 Due to the recognition of the issues of natural and synthetic ACEM materials, a series of strategies had been proposed to enhance their surface functional properties. [22][23][24] Hongsriphan and Sanga 25 applied chitosan solutions with different concentrations (0.25, 0.50, 1.00, and 2.00% w/v) to deposit an antibacterial layer on the surface of PLA; the results showed that the chitosan coating had enhanced the water vapor transmission rate, mechanical properties, and antibacterial activity against Staphylococcus aureus and Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of these biomass materials are cheap, rich resources and easy availability. 21 Due to the recognition of the issues of natural and synthetic ACEM materials, a series of strategies had been proposed to enhance their surface functional properties. [22][23][24] Hongsriphan and Sanga 25 applied chitosan solutions with different concentrations (0.25, 0.50, 1.00, and 2.00% w/v) to deposit an antibacterial layer on the surface of PLA; the results showed that the chitosan coating had enhanced the water vapor transmission rate, mechanical properties, and antibacterial activity against Staphylococcus aureus and Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the thermoresponsive layers with visible light photocatalytic activity, plasmonic Ag-TiO 2 photocatalyst nanoparticles were incorporated into the PDSM/PNIPAAm copolymer matrices. As it is detailed in our previous publications, the catalyst and its composites exhibit visible light photoactivity (λ abs,max ~ 450 nm; E g = 3.08 eV band gap energy) with excellent photodegradation-efficiency against organic pollutants, and antimicrobial activity in many scenarios [33,34,[44][45][46]. By dispersing 15 wt% Ag-TiO 2 photocatalyst nanoparticles in the doctor blade-casted and spray-coated layers of PDMS-co-INI matrix, Ag-TiO 2 /PDMS-co-INI composite layers were formed.…”
Section: General Sample Characterizationmentioning
confidence: 90%
“…Raman microscopy measurements were performed with a Thermo Scientific DXR Raman microscope (Thermo Fisher Scientific; Waltham, MA, USA). A laser-light of 780 nm wavelength was used, and its Mérai et al -Express Polymer Letters Vol.16, No.1 (2022) [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] maximum power was 24 mW. The microscopic lenses used for measurements were magnified 50×, and the aperture was 25 µm.…”
Section: Raman-microscopymentioning
confidence: 99%
See 2 more Smart Citations